Аirport vicinity zoning as a method of limiting of the aircraft impact on environment - Zaporozhets O.І.; Konovalova О.V.; Stetsenko N.М.; Kozhushko О.М. (Proceedings of National Aviation University (archive), 2006)
Compatibility policies, including both criteria and maps, are the central component of any compatibility plan of the airport. The purpose of this article is to discuss basic concepts and common issues involved in preparing an airport land use compatibility plan and in formulating the policies contained therein.